2021
DOI: 10.13040/ijpsr.0975-8232.12(7).3858-65
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Anxiety disorders are among the most prevalent and high-cost diseases. Medicinal plants are a very good option to treat, and several have shown the ability to reduce anxiety. We report here the effect of A. gratissima var. gratissima (Agg) on behavior and anxiety in mice. The methanol extract of leaves was tested in order to verify the safety, effect on sleeping time and behavior. Anxiety was tested through the Open field, Hole board, and elevated plus maze tests, with 50, 100, 200, and 400 mg/kg of Agg, and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 24 publications
4
2
0
Order By: Relevance
“…Nevertheless, a statistically significant increase in swimming time was observed in animals treated with all doses of the extract, as expected. These results agree with the reported effect on sleep time induced by barbiturates [21], thus indicating that Agg exerts its antidepressant effect without exerting a stimulating effect on the CNS [31].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Nevertheless, a statistically significant increase in swimming time was observed in animals treated with all doses of the extract, as expected. These results agree with the reported effect on sleep time induced by barbiturates [21], thus indicating that Agg exerts its antidepressant effect without exerting a stimulating effect on the CNS [31].…”
Section: Discussionsupporting
confidence: 92%
“…Taking this into account, and the differences between our result with the ethanolic extract of A. gratissima var. gratissima and the anxiolytic effect reported [21], it could indicate, as a possible mechanism of action of the antidepressant effect, a set of interactions with other receptors not studied by Zeni et al, for which the tail suspension method is not sensitive enough, such as the inhibition of MAO or interaction with the GABA A receptor [33][34][35].…”
Section: Discussionmentioning
confidence: 91%
“…platyphylla has an anxiolytic-like effect (30). Several species of Verbenaceae, particularly Aloysia, demonstrated an anxiolytic effect (12,(14)(15)(16)18,(20)(21)(22), and our results agree with that.…”
Section: Hole-board Assaysupporting
confidence: 91%
“…platyphylla showed no adverse effect in the acute toxicity test. A similar result was observed with A. gratissima var gratissima(14). The barbiturate-induced sleep time test indicated that this plant is devoid of depressant or stimulant effects on the central nervous system(28), while animals treated with diazepam prolonged sleep time as expected for this drug used as the positive control.Mice treated with diazepam and 50, 100, and 200 mg/kg of the methanolic extract of A. virgata var.…”
supporting
confidence: 70%
See 1 more Smart Citation